The Impact of Project Based Learning with Aquascapes on Metacognitive Skills and Learning Outcomes in Ecosystem Lesson - Linda Murisqa; Muhibbuddin; Safrida; Cut Nurmaliah; Abdullah (Postgraduate, University of Mataram, 2024)
This study aims to determine the effect of the Project-Based Learning (PjBL) model based on aquascape media on students' metacognitive abilities and learning outcomes in ecosystem material. The research used a Pretest-Posttest Control Group experimental design, consisting of control and experimental classes. The population of the study included 241 tenth-grade students at SMAN 1 Idi Rayeuk, with a sample of 68 students determined through random sampling techniques. Data on metacognitive abilities were collected using a metacognitive state inventory, while learning outcomes were measured using written tests. Data analysis employed the Independent-Sample T test to analyze the impact of the PjBL model based on aquascape media on metacognitive abilities and learning outcomes. The results showed that the PjBL model had a significant effect on metacognitive abilities with a p-value of 0.030 (p < 0.05), as well as a significant effect on learning outcomes with a p-value of 0.000 (p < 0.05). In conclusion, the PjBL model based on aquascape media has a positive effect on enhancing students' metacognitive abilities and learning outcomes in ecosystem material.